2021
DOI: 10.3390/molecules26165028
|View full text |Cite
|
Sign up to set email alerts
|

Black Garlic and Its Bioactive Compounds on Human Health Diseases: A Review

Abstract: Black garlic (BG) is a form of aged garlic obtained from raw garlic (Allium sativum) via Millard reaction under high temperature (60–90 °C) and humidity (70–90%) for a period of time. Several studies reported higher contents of water-soluble antioxidants compounds (S-allyl cysteine, S-allyl-mercapto cysteine), 5-hydroxymethylfurfural, organosulfur compounds, polyphenol, volatile compounds, and products of other Millard reactions compared to fresh garlic after the thermal processing. Recent studies have demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 159 publications
(224 reference statements)
0
52
0
2
Order By: Relevance
“…Garlic samples heated at low temperatures (60 °C) had more SAC content than at high temperatures (80 °C) because low temperature can promote the transformation of GSAC to SAC by γ-GTP better than at high temperature 13 . This agreed with the previously reported findings of Ahmed & Wang 13 that the optimum temperature for γ-GTP activity was 40 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Garlic samples heated at low temperatures (60 °C) had more SAC content than at high temperatures (80 °C) because low temperature can promote the transformation of GSAC to SAC by γ-GTP better than at high temperature 13 . This agreed with the previously reported findings of Ahmed & Wang 13 that the optimum temperature for γ-GTP activity was 40 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies show that AGE treatments can even decrease IL-1β levels in the hippocampus [78] (Figure 5). In studies using LPS-treated cell cultures, aged garlic extracts were proved to have the ability to reduce levels of NO and inflammatory cytokines, such as IL-6 and TNF-α, in addition to decreasing the expression of COX-2 and iNOS [80].…”
Section: Sac/garlicmentioning
confidence: 99%
“…In the context of nutritional supplements, the actions of Palmitoylethanolamide (PEA) are notable. This is an endocannabinoid-like lipid mediator with extensively In studies using LPS-treated cell cultures, aged garlic extracts were proved to have the ability to reduce levels of NO and inflammatory cytokines, such as IL-6 and TNF-α, in addition to decreasing the expression of COX-2 and iNOS [80].…”
Section: Palmitoylethanolamide (Pea)mentioning
confidence: 99%
See 1 more Smart Citation
“…(15) In Ahmed et al (2021) research it was found that black garlic, after going through pre-clinical and clinical studies, showed clear evidence that its consumption can be a supportive therapy for various diseases in humans . (16) Based on 8 journals that have been researched, it was found that in general black garlic extract has an Based on those 4 studies, it can be seen that the average fermentation is done at the temperature of 70-80C with 75-85% humidity for 28-40 days. This is following the journal Novel Nutritive Garlic Product "'Black Garlic'": A Critical Review of Its Composition, Production, and Bioactivity by Alihanoğlu S et al (2017) who said that fermentation to produce the best characteristic black garlic is done at high temperatures (70-80C) with 70-90% humidity for about 21 days.…”
Section: Contentmentioning
confidence: 99%